2018
DOI: 10.3390/met8010069
|View full text |Cite
|
Sign up to set email alerts
|

Direct Production of Ferrochrome by Segregation Reduction of Chromite in the Presence of Calcium Chloride

Abstract: Abstract:A solid reduction process is described whereby chromite is reduced with the help of calcium chloride to produce ferrochrome alloy powders with high metal recovery. The process involves segregation reduction of chromite using graphite as the reductant and calcium chloride as the segregation catalyst. Experiments were performed in the temperature range of 1200-1400 • C to evaluate the influences of various design parameters using both a thermogravimetric analyzer and an electric tube furnace with contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 18 publications
3
11
0
Order By: Relevance
“…As seen, the sizes of metallic Fe particles are generally in the range of 100-200 µm, which are much larger comparing to those formed in the absence of CaCl 2 (e.g., <40 µm as shown in Figure 6b, with 4 h reduction). The promoting effects of CaCl 2 addition on carbothermic reduction of Mn ore observed in the study was similar to that revealed during CaCl 2 -assisted carbothermic reduction of chromite ore [28,29], indicating a similar role played in the reduction process. CaCl 2 became molten at the reduction temperature of 1000 • C, because its melting point is 775 • C [33].…”
Section: Influence Of Cacl 2 Additionsupporting
confidence: 84%
See 2 more Smart Citations
“…As seen, the sizes of metallic Fe particles are generally in the range of 100-200 µm, which are much larger comparing to those formed in the absence of CaCl 2 (e.g., <40 µm as shown in Figure 6b, with 4 h reduction). The promoting effects of CaCl 2 addition on carbothermic reduction of Mn ore observed in the study was similar to that revealed during CaCl 2 -assisted carbothermic reduction of chromite ore [28,29], indicating a similar role played in the reduction process. CaCl 2 became molten at the reduction temperature of 1000 • C, because its melting point is 775 • C [33].…”
Section: Influence Of Cacl 2 Additionsupporting
confidence: 84%
“…Metals 2019, 9, x FOR PEER REVIEW 9 of 17 assisted carbothermic reduction of chromite ore [28,29], indicating a similar role played in the reduction process. CaCl2 became molten at the reduction temperature of 1000 °C, because its melting point is 775 °C [33].…”
Section: Influence Of Cacl 2 Additionmentioning
confidence: 96%
See 1 more Smart Citation
“…This would make NaCl not desirable as a flux. As discussed in our earlier publications, an effective accelerant must have a boiling point that is much higher and melting point that is lower than 1300°C, the optimum direct reduction temperature (Sokhanvaran and Paktunc, 2017a;Sokhanvaran, Paktunc, and Barnes, 2018;Yu and Paktunc, 2017, 2018a, 2018b.…”
Section: Influences Of Alkali Fluxes On Direct Reduction Of Chromite mentioning
confidence: 98%
“…Since the filing of the patent application on the use of several alkalis as the accelerants (Winter, 2015; Barnes, Muinonen, and Lavigne, 2015), we have been performing systematic studies to improve our understanding of the roles of various fluxes. Our studies involved using NaCl, NaOH, Na 2 CO 3 , CaCl 2 , Ni, and a metallurgical waste product as the fluxes in accelerating the reduction of chromite and developing a fundamental understanding of the kinetics and mechanisms of reduction and metallization Paktunc, 2017, 2018;Sokhanvaran, Paktunc, and Barnes, 2018;Yu and Paktunc, 2017;Yu and Paktunc, 2018a, 2018b, 2018c. These studies formed parts of the broader research into improving and optimizing the conventional smelting processes as well as developing new reduction technologies to reduce energy demands and greenhouse gas emissions, and evaluating the Influences of alkali fluxes on direct reduction of chromite for ferrochrome production by D. Paktunc*, Y. Thibault*, S. Sokhanvaran*, and D. Yu* Prereduction and flux-aided direct reduction of chromite provide significant advantages in reducing energy consumption and greenhouse gas emissions during ferrochrome production.…”
mentioning
confidence: 99%